Conflict Of Authority And Social Policy North Sumatera - Syahminan; Katimin (CV. AFDIFAL MAJU BERKAH, 2022)
The conflicts that occurred gave an understanding that North Sumatra is not socially desolate from conflict, researchers see that the conflict that occurred in North Sumatra is essentially indicated sara conflict (ethnic, religious, racial and Intergroup) related to economic issues, politics, law and social injustice of the owner of authority. Although the researcher's view is still debatable, and there are those who hold the opposite view but according to the researcher only for reasons of temporary tranquility, even counter-productive and not solutive, which tends to remain silent is not solved wisely. The case-asus conflict is not pure sara, but the real driver is sara factor. Although not all conflicts are caused by sara, but major cases that have a national impact can be categorized as sara's background Despite various prevention and synergy efforts by the authorities (government) with a number of economic, socio-religious, social ethnic, social cultural and socio-political policies. This is because conflict in society is theoretically an inevitability due to social interaction itself. But if the conflict continues to occur, it means that the community has problems as a sick society. The power of social immun against conflict is weak, because it requires the power and authority and policy in intervening (as a force to force) to be able to regulate society towards harmony and social goodness, either in the form of regulations, laws with sangsinya that regulate the course of social life towards a more harmonious. But the rules and regulations issued by the government are sometimes not enough to satisfy everyone, it can lead to new conflicts in society. This should certainly get attention. In addition, it is necessary that the culture has the values of local wisdom in addition to traditional figures, and charismatic figures who have social authority to create harmony of society, the latter as alleged researchers, especially charismatic figures no longer exist in the midst of society, if there are they are old, while the replacement is not there, as a result, the community does not have role models that can be seen policies in managing the community who use many non-formal means such as cultural policies (culture) as implemented by the governor of North Sumatra EWP. Tambunan in 1979, the conflict was resolved by cutting buffaloes and eating with all elements of society, speaking and showing heart and will so that everything is complete, while the court decisions issued by formal authorities, can only solve the problem on the surface, but not solve the problem satisfactorily.